Bearing Witness 2016: A Fiji Climate Change Journalism Case Study - Robie, D (Pacific Media Centre, School of Communication Studies, Auckland University of Technology, 2017)
In February 2016, the Fiji Islands were devastated by Severe Tropical Cyclone Winston, the strongest recorded tropical storm in the Southern Hemisphere. The category 5 storm with wind gusts reaching 300 kilometres an hour, left 44 people dead, 45,000 people displaced, 350,000 indirectly affected, and $650 million worth of damage (Climate Council, 2016). In March 2017, the Secretariat of the Pacific Regional Environment Programme (SPREP) launched a new 10-year Strategic Plan 2017-2026, which regards climate change as a ‘deeply troubling issue for the environmental, economic, and social viability of Pacific island countries and territories’. In November, Fiji will co-host the UN Framework Convention on Climate Change (COP23) climate change conference in Bonn, Germany. Against this background, the Pacific Media Centre despatched two neophyte journalists to Fiji for a two-week field trip in April 2016 on a ‘bearing witness’ journalism experiential assignment to work in collaboration with the Pacific Centre for the Environment and Sustainable Development (PaCE-SD) and the Regional Journalism Programme at the University of the South Pacific. This paper is a case study assessing this climate change journalism project and arguing for the initiative to be funded for a multiple-year period in future and to cover additional Pacific countries, especially those so-called ‘frontline’ climate change states.
Keywords: Bearing witness; Climate change; COP23; Environmental journalism; Fiji; Pacific Islands; Pacific Regional Environment Programme; SPREP